(3TQM GdaQGFV GdTgGHjIs - (3GdeScQj GdMfaj, YHO GdMdje, J (B900 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; Ydjc fJhcd heaGJjM GdbdhH HjOc jG cQje GdMeO ddg GdYdje GdMdje hGdUdGI Ydi QShdg GdcQje bGd GdbGVj TgGH GdOjf CHh MGeO eMeO CHj CMeO Hf Ydj Hf CHj WGdHs
(3BNQgG (B:s
(3aEf de jcf ehdi GdehdGI hde jhLO aGdeGd cdg dHjJ GdeGd hGYde Gf ehdi GdehdGI ebOe Ydi GdebQ dg HGdfSHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B2 / 61s
(3cTa GdXfhf (B2 / 1250s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdaQGFVs